Thermal inactivation of Listeria monocytogenes from alheiras, traditional Portuguese sausage during cooking - Felício, Maria Teresa S. (2012)
D values were calculated at 55, 60 and 65 °C for five Listeria monocytogenes isolates using alheira (traditional Portuguese sausage) food matrix as heating menstrum. z values were also calculated and combined with internal alheiras temperature profiles during cooking in multiple ways, allowed estimations of percentages of L. monocytogenes survival. Survival percentages estimations showed that except for roasting, the remaining evaluated cooking methods might not be sufficient to inactivate this foodborne pathogen in alheiras at the minimum temperature profiles. However, it is important to note that all evaluated cooking methods were able to inactivate L. monocytogenes in alheiras at their maximum internal temperature profiles